2007
DOI: 10.1002/mats.200700001
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Simulation of Uniaxial Deformation of Polyethylene‐Like Polymer Glass: Role of Constraints and Deformation Protocol

Abstract: The deformation of a glassy amorphous polymer has been simulated by Monte Carlo. A molecular model with constrained chemical bonds (rigid‐bond model) and one with chemical bonds represented by Gaussian springs (flexible‐bond model) have been compared. Furthermore, two different deformation protocols have been tested. Comparisons on the basis of stress–strain behavior, contributions of various interactions to stress and energy, evolution of density and distribution of dihedral angles, and of pair correlation fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…24,[26][27][28] Also other simulation techniques are applied to study the deformation of polymers, such as Monte Carlo algorithms or variants of energyminimization methods for PE-alike, 29 polypropylene, 30,31 poly͑oxypropylene͒, 32 PC, [33][34][35] and PE. 36,37 As the simulation studies are limited to only small time and length scales, numerical agreement is often only possible by means of extrapolation over orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…24,[26][27][28] Also other simulation techniques are applied to study the deformation of polymers, such as Monte Carlo algorithms or variants of energyminimization methods for PE-alike, 29 polypropylene, 30,31 poly͑oxypropylene͒, 32 PC, [33][34][35] and PE. 36,37 As the simulation studies are limited to only small time and length scales, numerical agreement is often only possible by means of extrapolation over orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…Coarse grain techniques [2][3][4][5], such as united atom models [6][7][8][9][10], have been widely used to simulate polymer systems at various length and time scales. For instance, previous work has used Monte Carlo methods and molecular dynamics (MD) simulations to study deformation mechanisms during uniaxial tensile deformation of amorphous polyethylene-like glassy polymers [8][9][10]. The stress-strain curves qualitatively show agreement with experimental results on amorphous polymers.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Hoy and Robbins [17][18][19] have used such coarse-grained bead-spring models to interrogate strain hardening in glassy polymers as a function of both microstructure and deformation conditions; they found that the plastic flow stress correlated with the strain hardening modulus, indicating that entropic network models used for rubber elasticity theory may not accurately capture the nanoscale physics of strain hardening in polymer glasses. Additionally, other simulations have used more chemically-realistic potential formulations for studying properties in specific systems (e.g., polyethylene [20][21][22][23][24]) as well as different numerical schemes for molecular deformation, such as Monte Carlo [8,9,25]. However, although several groups have studied the static, dynamic, and mechanical properties of glassy polymer systems, there is still much that is not understood with respect to polymer deformation simulations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations